Variations of the Earth's rotation rate and cyclic processes in geodynamics - B.W. Levin (Geodesy and Geodynamics, 2017)
The authors analyzed the relationship between variations of the Earth's rotation rate and the geodynamic processes within the Earth's body, including seismic activity. The rotation rate of a planet determines its uniaxial compression along the axis of rotation and the areas of various surface elements of the body. The Earth's ellipticity variations, caused naturally by the rotation rate variations, are manifested in vertical components of precise GPS measurements. Comparative analysis of these variations is considered in view of modern theoretical ideas concerning the Earth's figure. The results justify further research that is of interest for improvement of space systems and technologies.